Effect of surfactant on lycopene-loaded nanostructured lipid carriers. - Riangjanapatee,P. (International Advancement Center for Medicine & Health Research Co., Ltd. (IACMHR Co., Ltd.), 2015)
Nanostructured lipid carriers (NLC) have gained high interest as enhancing drug delivery systems via topical application during the last few years. NLC can enhance stability of many active substances against environmental stress. The extremely small size of NLC plays an important role in skin penetration. The unchanged size of NLC upon storage indicates its physical stability. The aim of this work was to investigate the effect of surfactant type on physical properties and stability of lycopene-loaded NLC. The preparation of the NLC was achieved by means of high pressure homogenization. The results indicate that different types of surfactant yield NLC with different properties. We also explored the effect of contact angle on the size of the NLC. It was found that the small contact angle gave NLC with small size. Among two small contact angle surfactants, Plantacare 1200 gave lycopene-loaded NLC with smaller size, higher zeta potential and narrower size distribution. The particle size, size distribution, and zeta potential of lycopene-loaded NLC prepared with Plantacare 1200 was unchanged during 30 days of storage. It was concluded that Plantacare 1200 is the most suitable surfactant for lycopene-loaded NLC. The chemical stability of lycopene entrapped in the NLC was significantly enhanced.